Magnetic effect on the phase properties of neodymium-activated yttriumdisilicate nanomaterials - (:unkn) unknown (My University, 2016)
0

Under varying temperature conditions, undoped Y2Si2O7and neodymium-doped Y2Si2O7nanopowderswere synthesized by the sol-gel method. The phase transitions fromto?were observed in neodymium nanopowdersby XRD measurements. TEM images showed ball-shaped structure forms for synthesized samples. The elementalcompositions of all samples were established and quite close stoichiometry to all compound formulas was found usingan attached component for TEM. To reveal the Nd dopant effect in different-phased Y2Si2O7nanopowders, diffusere ectance measurements were conducted. To establish the magnetic properties of undoped Y2Si2O7and neodymium-doped Y2Si2O7nanopowders, an extensive study was carried out including M-H, M2-H/M (Arrott's plot), and M-Tunder varying physical conditions. In thephase, a signi cant paramagnetic increase was observed and a decrease inparamagnetic behavior was monitored by the effects of Nd dopant and increased annealing temperature.
Keywords: Fizik, Uygulamalı